The study of dynamic load on a wagon–platform at a shunting collision - Lovskaya, Alyona; Ryibin, Andrey (Eastern-European Journal of Enterprise Technologies, 2016)
In order to increase the volume of cargo transportation through international transport corridors that pass through Ukraine, container transportation has been developed. To ensure the safety of a wagon-platform with containers placed on it, the research of dynamic loads acting on them at shunting collision has been conducted in real operating conditions. The research results led to the conclusion that the largest values of acceleration acting on the wagon-platform with containers placed on it during a shunting collision occur in the presence of gaps between the fitting stops and fittings and amount, respectively, about 90 m/s² and 110 m/s². The approbation of obtained acceleration values was performed by computer simulation of the dynamics of a wagon platform with containers placed on it under the action of the longitudinal impact force of 3.5 MN on the back gauge of automatic coupling. Verification of the model was tested by the Fischer criterion. This revealed that the hypothesis of the adequacy of the model was not disputed. Conducted research will improve operational safety of the wagons in the combined transportation, and will motivate design of wagons of the new generation for use in combined international traffic.